Effect of CFIm68 knockdown on RNA polymerase II transcription - Tellier, M; Hardy, J; Norbury, C; Murphy, S (BioMed Central, 2019)
Objectives Transcription of eukaryotic protein-coding genes by RNA polymerase II (pol II) is highly regulated at initiation, elongation and termination. Transcription is also coordinated with co-transcriptional processing of the emerging pre-mRNA by capping, splicing, and cleavage and polyadenylation. Polyadenylation (poly(A)) site recognition, which defines the end of the mRNA, relies on the cleavage and polyadenylation (CPA) complex. It was previously observed that knocking-down proteins of the CPA complex affects not only recognition of the poly(A) site but also results in increased pausing of pol II at the beginning of genes. This finding suggests that the CPA complex plays a role in regulating pol II turnover after transcription initiation. Data description To explore this possibility, we knocked-down a subunit of the cleavage factor I (CFIm), CFIm68, which is part of the CPA complex and involved in alternative polyadenylation, and performed pol II ChIP-seq in absence or presence of a transcription elongation inhibitor. In addition, we performed pol II ChIP-qPCR on a subset of protein coding genes after knocking down CFIm68.